TRADITIONAL INSURANCE AGENCY COMMUNICATION MANAGEMENT: A CASE STUDY AT PANIN DAI-ICHI LIFE BANDUNG BRANCH WEST JAVA - Nursafitri, Meicinda; Lusy Mukhlisiana (International Journal of Cultural and Social Science, 2025)
This study evaluates the effectiveness of internal communication between management and agents in a traditional insurance company, focusing on Panin Dai-ichi Life Bandung Branch. Using a qualitative descriptive approach with six agent informants, findings reveal a predominantly one-way communication flow with insufficient dialogue, unclear instructions, and a lack of structured feedback, leading to decreased motivation and performance. Agents proposed the establishment of regular two-way communication forums, interpersonal training for managers, and anonymous feedback channels. The study concludes that enhancing internal communication requires a systemic strategy, including leadership transformation and participatory culture. These findings offer a practical framework for developing adaptive and sustainable communication strategies in traditional insurance agencies facing industry competition.